Performance and Exergy Analyses of GT-MHR Nuclear Cycles - Akçay, Enes; Arzu Keven; Karaali, Rabi (International Journal of Computational and Experimental Science and Engineering, 2026)
In this study, the performance and exergy analyses of the GT-MHR type nuclear power plants with high thermal energy were analysed. The GT-MHR (Gas Turbine-Modular Helium Reactor), produces electricity by using helium gas in the Brayton cycle, and utilizes the waste heat of the system with the Rankine cycle. The Brayton cycle allows helium gas to be heated to high temperatures in the reactor core, then converted into mechanical energy by using a gas turbine. This hybrid structures in the designs of GT-MHRs allow the combined use of nuclear and renewable energy sources.It was found that exergy efficiency reached its maximum level between approximately 14,000 - 16,000 kPa. At this point, the exergy losses of this system approach its lowest level and the components reach the most ideal operating conditions. If the system is operated below or above of this value, the total exergy efficiency will decrease. The exergy efficiency, which is initially approximately 74.5% at 500 kPa pump pressure, increases to 75.1% at 1000 kPa pressure level. While the pump pressure at 500 kPa produces a work of approximately 532,000 kW, at 1000 kPa it increases to 560,000 kW. Thus, GT-MHR pioneers the energy technologies of the future by combining both high efficiency and environmental sustainability.